Virtual Machines In Education - Mateljan, Vladimir (Array, 2014)
Virtualization finds wide application in information and communication technology. Some of these applications can be used in education, to simplify the administration and teaching performance while saving money. In the last few years, computer technology has progressed sufficiently thus facilitate the development of virtual machines that provide a completely new method of using computers and their resources. The virtual machine is a software implementation of a machine that executes programs like a physical machine. There are several types of virtualization, span from partial to complete, and most of them could find a useful application in education. Setting up test environments, virtualization of classroom for a particular course, remote connection, and use of existing computer without any hardware upgrades, faster backup, and easier maintenance are some of the benefits of implementing virtual machines in education.